Conversação e emoção em emissões nocturnas de rádio : a ironia verbal como tropo ilocutório e como estratégia discursiva de gestão interaccional do conflito - Almeida, Carla Aurélia de (2015)
Taking as reference an oral corpus consisting of verbal interactions presented in Portuguese radio phone-in programmes and a specific set of broadcasts dedicated to the discussion of polemic institutional processes, we proceed to the identification of varieties of verbal irony. Considering emotion in the frame of interactional work developed by interactants in conversation (Edwards, 2001: 236), we analyse aggressive irony, such as sarcasm and the rhetorical figures that build conversational involvement and give a humoristic tone to discourse: hyperbole, repetitions, Extreme Case Formulations (=ECFs). After this, we take irony as an illocutionary trope and the discursive strategies of face work. Finally, we consider citation irony that, in these contexts, creates an axis of enunciative heterogeneity, having specific argumentative effects.